VITAMIN PREVENTIVE ALGORITHM FOR CHILDREN WITH ACUTE RESPIRATORY DISEASES: TECHNOLOGY OF INCREASING NON SPECIFIC RESISTANCE - O.A. Gromova; V.G. Rebrov ("Paediatrician" Publishers LLC, 2007)
An algorithm of choosing adequate vitamin combination for children's acute respiratory diseases is suggested on the basis of Pikovit vitamin complex (KRKA, Slovenia). It is emphasized that the choice of vitamins should be based on the peculiarities of their metabolism and their role in the body. The importance of vitamin therapy is in its immunomodifying effect and increasing child's abilities for adaptation. Choice of vitamin and mineral complex for seasonal child ARD prevention depends on physiological vitamin doses and the fact that vitamin and mineral complexes containing iron and copper should be excluded in the acute phase of the disease. Latest research data is provided demonstrating the inadvisability of using iron and copper additives to children with ARD. The article provides information on the necessity of qualified primary inspection of the sick child, diagnosing activities, composing an individual diet, vitamin and pharmacological therapy. Key words: polyvitamin products, prevention, acute respiratory infections, children.